2015
DOI: 10.1107/s1399004715003053
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of the X-ray-induced enzymatic reaction of octahaem cytochromecnitrite reductase

Abstract: Octahaem cytochrome c nitrite reductase from the bacterium Thioalkalivibrio nitratireducens catalyzes the reduction of nitrite to ammonium and of sulfite to sulfide. The reducing properties of X-ray radiation and the high quality of the enzyme crystals allow study of the catalytic reaction of cytochrome c nitrite reductase directly in a crystal of the enzyme, with the reaction being induced by X-rays. Series of diffraction data sets with increasing absorbed dose were collected from crystals of the free form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…14,15 The crystallographic studies revealed CcNiR to be a homodimeric multiheme enzyme in all bacterial organisms except in the haloalkaliphilic bacterium T. nitratireducens. 14 The latter exists as a stable hexamer containing 48 hemes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The crystallographic studies revealed CcNiR to be a homodimeric multiheme enzyme in all bacterial organisms except in the haloalkaliphilic bacterium T. nitratireducens. 14 The latter exists as a stable hexamer containing 48 hemes.…”
Section: Introductionmentioning
confidence: 99%
“…The inelastic interactions of X- rays with the protein in the crystal during data collection can lead to crystal radiation damage and different chemical modifications of the protein 70 . One specific effect of radiation damage to the protein is the reduction of some metal ions 7173 . During the crystallographic experiment, it is important to consider and address the possibility of the metal reduction, especially if the metal is expected to be in a higher oxidation state when multiple oxidation states are possible in a protein-metal complex.…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic X-ray scattering produces photoelectrons that can change the oxidation state of metals in the active sites of redox enzymes and cause an enzymatic reaction (Garman, 2010). The serial single-crystal method had previously been applied to study enzymatic catalysis in crystals of metal-mediated reductases (Trofimov et al, 2015;Horrell et al, 2016). The connection of the copper-ion oxidation to its coordination at photoreduction has been explored in the case of monooxygenases (Hemsworth et al, 2013;Gudmundsson et al, 2014;Frandsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%